2023
DOI: 10.3389/fpls.2023.1132024
|View full text |Cite
|
Sign up to set email alerts
|

Differential analysis of transcriptomic and metabolomic of free fatty acid rancidity process in oil palm (Elaeis guineensis) fruits of different husk types

Abstract: IntroductionOil palm is the world's highest yielding oil crop and its palm oil has high nutritional value, making it an oilseed plant with important economic value and application prospects. After picking, oil palm fruits exposed to air will gradually become soft and accelerate the process of fatty acid rancidity, which will not only affect their flavor and nutritional value, but also produce substances harmful to the human body. As a result, studying the dynamic change pattern of free fatty acids and importan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The changes in free fatty acid content of two fruit varieties were examined at different time points after postharvest. The study reported on the levels of free fatty acids at 0 h, 24 h, and 36 h., Additionally, candidate genes that may play a role in regulating these changes in free fatty acid content were identified [22]. By combining metabolomics and transcriptomics analysis of changes in free fatty acids during the development stage of oil palm fruits is crucial in understanding the metabolic processes that occur during this period., By identifying the key genes involved in the production of free fatty acids, valuable insights into the factors that influence oil accumulation in oil palm fruits can be gained.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in free fatty acid content of two fruit varieties were examined at different time points after postharvest. The study reported on the levels of free fatty acids at 0 h, 24 h, and 36 h., Additionally, candidate genes that may play a role in regulating these changes in free fatty acid content were identified [22]. By combining metabolomics and transcriptomics analysis of changes in free fatty acids during the development stage of oil palm fruits is crucial in understanding the metabolic processes that occur during this period., By identifying the key genes involved in the production of free fatty acids, valuable insights into the factors that influence oil accumulation in oil palm fruits can be gained.…”
Section: Introductionmentioning
confidence: 99%